Ovarian hyperstimulation syndrome complicating spontaneous molar pregnancy: a case report - Mishra, Abhishek; Gaire, Sushila; KC, Bipana; Mahat, Pradeep; Neupane, Jeevan; Chaubey, Mandip (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Ovarian hyperstimulation syndrome (OHSS) is a rare finding that occurs in early pregnancy. There is a rapidly increasing ovarian size secreting vasoactive substances that lead to fluid shift into third spaces. It can be associated with a spectrum of other clinical findings, including ascites, hemoconcentration, hypercoagulability, and electrolyte imbalances. OHSS most commonly occurs as a complication of treatment with in vitro fertilization medications, such as human chorionic gonadotropin (hCG) or gonadotropin-releasing hormone agonists. OHSS has infrequently been reported to be caused by high hCG levels in molar pregnancies. We present a case of OHSS complicating spontaneous molar pregnancy. A 25‑year gravida 3, para 2+0, living 2 lady presented with complaints of continuous vaginal bleeding for 2 weeks and lower abdominal pain at 17 weeks' gestation. A bulky uterus containing a large hyperechoic structure with multiple cystic spaces suggestive of complete molar gestation and enlarged ovaries containing multiple cysts were seen on ultrasound imaging. She was managed successfully with conservative and supportive treatment.